Implementasi Peraturan Menteri Perhubungan No. 10 Tahun 2011 Tentang Persyaratan Teknis Peralatan Persinyalan Perkeretaapian Terhadap Teknologi Communication Base Train Control (CBTC) Di PT. MRT Jakarta - Oktaria, Dhina Setyo (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
The development of railroad transportation which is increasingly rapid needs to be made provisions that can support safety, one of which is stipulated in the regulation of the minister of transportation No. 10 of 2011 concerning Technical Requirements for Railway Based Communication Control Train (CBTC) Railway Equipment that will be applied at PT MRT Jakarta so that research is needed to test the relevance of the regulation. The method used in this study is Normative Juridical namely normative legal research method or library legal research method is the method or method used in legal research conducted by examining existing library materials. The collected data is analyzed by comparing current regulations with CBTC technology that will be applied at PT. Jakarta MRT. The results of this study can be seen that there are some specifications of the equipment that are appropriate, not suitable and even there are also completely different between the provisions in PM No. 10 of 2011 concerning Signaling Technical Requirements.